Climatic factors and establishment of Quercus ilex-communities in Trieste Province (NE Italy) (Annali di Botanica, 2004)
In the coastal area called "Cernizza" (near Duino. ca 15 km NW from Trieste), at an altitude between 0 and 40 m. is located a wood vegetation complex characterized by Quercus ilex and Carpinus orientalis. The bedrocks of this site is carbonatic. This wood vegetation does not occur in other sites or the Trieste province, where deciduous oak woods (Q. pubescells, Q. petraea s.1.) are dominant both on arenaceus and on carbonatic rocks. Other Quercus ilex communities are occurring only as scrubs on the calcareous coastal cliffs characterized by primitive lithosoils. In order to detect if this wood community might be an expression of the c1imate dominating this particular zone, some Duino's c1imatic data, relative lo a record period of 9 years. have been compared with the Trieste's ones. The analysed parameters were the following: air temperature. rainfall, evaporation. wind speed and relative humidity. From the comparison of these paramenters it emerged that the Duino's climate is more humid than the Trieste's one. Only in springtime Duino is less rainy than Trieste according lo the analysis of the monthly mean values of precipitation. From the ecophysiological point of view, a study of the seasonal changes of the root hydraulic conductance in some forest trees (Nardini el al .. 1998) has pointed out the superiority of Quercus ilex compared to Quercus pubescens, as regards the competitive ability of the seedlings during the spring. For this reason, the smaller spring rainfall could explain the occurrence of Quercus ilex stands not only in the neighbourhood of Duino but also at the beginning of the large valleys characterized by S•N direction in the South Eastern Alps.